Inside Cover: Photocatalytic CO2 Reduction by Periodic Mesoporous Organosilica (PMO) Containing Two Different Ruthenium Complexes as Photosensitizing and Catalytic Sites (Chem. Eur. J. 43/2017). Issue 43 (14th June 2017) - Kuramochi, Yusuke; Sekine, Masato; Kitamura, Kyohei; Maegawa, Yoshifumi; Goto, Yasutomo; Shirai, Soichi; Inagaki, Shinji; Ishida, Hitoshi
Abstract : Periodic mesoporous organosilicas (PMOs) modified with two different ruthenium complexes were synthesized and their catalytic activities for photochemical CO2 reduction were investigated. In the catalysis, [Ru(bpy)3 ]‐ and trans (Cl)‐[Ru(bpy)(CO)2 Cl2 ]‐type complexes act as the photosensitizer and the catalyst, respectively, to produce CO and HCOO − . More information can be found in the Full Paper by S. Inagaki, H. Ishida et al. onpage 10301 .